Geoffrey Colin Harcourt (1931-2021): A Cambridge economist from Down Under - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2022)
The paper offers a view of Geoff Harcourt's - b. 1931 in Melbourne; d. 2021 in Sydney - life trajectory as an Australian economist educated and active in the Cambridge UK tradition. His main contributions - to the Cambridge capital debates, history of economic thought and post-Keynesian economics - are discussed against aspects of his biographical background.
Keywords: B31; B50; 330; Harcourt; biography; capital debates; post-Keynesianism; history of economics